Strategi Pemecahan Permasalahan Kredit Bermasalah Nasabah Di BPR Nusamba Rambipuji Jember - Moh Luqman; Badrut Tamam (CV. ITTC INDONESIA, 2023)
BPR Nusamba Rambipuji Jember is a business entity that operates in Credit, Savings and Deposit products. Of course, carrying out these operations cannot be separated from the friction faced in its operations, especially in credit products. At BPR Nusamba Rambipuji Jember itself, in preserving and succeeding its business entity, it has a special strategy that is different from other institutions. However, it cannot be denied that every product will definitely not run smoothly, of course there are certain obstacles that it will face. Problematic credit is a problem that really needs to be paid attention to in running this business, there are many debtors who are sometimes unable to pay the principal and interest installments, but BPR Nusamba Rambipuji will not let this happen and develop by itself, of course it will be faced with various kinds of problems. method at BPR Nusamba Rambipuji Jember. In resolving Problematic Credit at BPR Nusamba Rambipuji Jember, the following strategy is carried out: BPR Nusamba Rambipuji carried out Credit Restructuring Legal Process Collateral Expropriation Write Off Books and Write Off Bills, however, since the establishment of BPR Nusamba until now, they have never done a Write Off Bill. This is a strategy used by BPR Nusamba Rambipuji Jember in dealing with Problematic Credit Products, where this is contained in the Credit Policy & Procedure Manual (PKPP) BPR Nusamba Rambipuji Jember from year to year which has been revised in accordance with the rules and authority of the Financial Services Authority and the Deposit Insurance Corporation (LPS).